ANALISIS HUBUNGAN SELF ACCEPTANCE DENGAN KEPATUHAN PENGOBATAN ARV PADA ORANG DENGAN HIV - Ramli, Kamrianti; Witari, Ni Nyoman Deni; Hermansyah, Hermansyah; Putra, Ryryn Suryaman Prana (Ensiklopedia of Journal, 2025)
Abstract: One of the health problems that is still a serious concern and raises concerns among the people of Indonesia is HIV/AIDS. Based on document searches, according to information from KPA Semarang Regency, cases are found to increase every year. From June 2022, there were 960 people affected by HIV. Bergas area with the first rank most HIV cases found with 115 cases. The purpose of the study was to determine the relationship between self-acceptance and adherence to ARV treatment in people with HIV. The research design used in this study was cross sectional. The research was conducted in the working area of the Bergas District Health Center in November 2024. The population was ODHIV who came to the Bergas District VCT clinic with a total of 115 ODHIV obtained from visit data at the VCT clinic. The sample amounted to 85 respondents. The sampling technique used in this study was Accidental Sampling. Data analysis was conducted univariately and bivariately. The results showed that there was a relationship between Self Acceptance and adherence to taking medication with a p value of 0.01. It is recommended to the family of ODHIV to always provide support and motivation to ODHIV.Keywords: HIV, Penerimaan Diri, VCT